1998
DOI: 10.1137/s105262349630060x
|View full text |Cite
|
Sign up to set email alerts
|

On the Nesterov--Todd Direction in Semidefinite Programming

Abstract: We study different choices of search direction for primal-dual interior-point methods for semidefinite programming problems. One particular choice we consider comes from a specialization of a class of algorithms developed by Nesterov and Todd for certain convex programming problems. We discuss how the search directions for the Nesterov-Todd (NT) method can be computed efficiently and demonstrate how they can be viewed as Newton directions. This last observation also leads to convenient computation of accelerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
200
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 216 publications
(203 citation statements)
references
References 14 publications
2
200
0
1
Order By: Relevance
“…The method used here differs in that we should guarantee the feasibility at each iteration. In addition, the Nesterov-Todd symmetrization scheme [48] is employed.…”
Section: Numerical Experimentsmentioning
confidence: 99%
“…The method used here differs in that we should guarantee the feasibility at each iteration. In addition, the Nesterov-Todd symmetrization scheme [48] is employed.…”
Section: Numerical Experimentsmentioning
confidence: 99%
“…As in [30], we only consider P such that P XY P −1 is symmetric. We also assume P is an analytic function of X, Y 0.…”
Section: Definition and Basic Properties Of Off-central Pathsmentioning
confidence: 99%
“…Similar to [30], it can be shown that the matrix in (12) is invertible for all X, Y 0 under Assumption 2.2(b).…”
Section: Qedmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, it is shown in Kojima, Shida and Shindoh 466 that the NT direction is a member of the KSH family the corresponding H is not so simple to describe. On the other hand, the AHO direction is not in the KSH family since, as opposed to the directions of the KSH family, the AHO direction does not necessarily exist at every point X;y;S 2 P + IR m P + see the discussion before Theorem 3.2 of Todd et al 831 .…”
Section: Endmentioning
confidence: 99%